The Intersection of Philosophy and Literature: Exploring Ideas and Reality (Sastra Inggris UNPAM, 2024)
The study of literary philosophy is a relatively new field in Indonesia, though it cannot be said to be a completely new discipline globally. There is growing optimism that the philosophy of literature will attract significant interest due to its unique advantages and distinct focus. This field explores the intersection of philosophy and literature, encompassing both written and oral traditions. This intersection offers a rich area for exploration, both in the realm of ideas and the tangible world. Philosophy and literature both concern themselves with the human experience, examining relationships between individuals, the divine, nature, life, and various existential issues. As a new branch of its parent discipline, the